Agricultural concentration and cropwise changes in Thanjavur district, Tamilnadu using geographical information system - Punithavathi, J; Tamilenthi, S; Baskaran, R (International Multidisciplinary Research Journal, 2012)
The paper presents an overview of agricultural cropping concentration and crop wise changes in Thanjavur district. The study area is mainly for plain area topography and “Rice bowl of Tamilnadu”. The study area is mainly suitable for climatic conditions, so the agriculture production is high. But recently the agricultural production is slowly decreased. Data of cropping pattern or concentration is taken for 10 years crop wise changes and used for analysis. The data’s collected were all secondary sources of information from statistical office and soil survey offices in Thanjavur district. The study area extends to an area of 3397sq k.ms. The District is divided into 8 taluks and 14 blocks with a total population of 2,402,781 persons according to 2011 census. The district is located in the Eastern coast of Tamil Nadu. The study area is consist of 14 toposheets and the scale of 1:50,000. Based on the data of crop-wise changes the data analysed using GIS for mapping.